(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The importance of education has been recognized by every civilization. Prior to the twentieth century, only a few females were granted access to education. Despite of the recognition of the significance of female education, there are many barriers in their way to higher education to give their cent percent input for the betterment of society in Indian context.